General Riemann-Hilbert problem with discontinuous coefficients for Moisil-Theodoresco system with junior members - Matiukaitė, Rima (Lietuvos matematikos rinkinys, 1997)
For Moisil–Theodoresco system with junior members a problem of new type, called Riemann–Hilbert problem with discontinuous coefficients, is considered. Under certain conditions this problem is proved to have Fredholm property for the mentioned system.